2021
DOI: 10.3390/mi13010034
|View full text |Cite
|
Sign up to set email alerts
|

Rapid AC Electrokinetic Micromixer with Electrically Conductive Sidewalls

Abstract: We report a quasi T-channel electrokinetics-based micromixer with electrically conductive sidewalls, where the electric field is in the transverse direction of the flow and parallel to the conductivity gradient at the interface between two fluids to be mixed. Mixing results are first compared with another widely studied micromixer configuration, where electrodes are located at the inlet and outlet of the channel with electric field parallel to bulk flow direction but orthogonal to the conductivity gradient at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It should be noted that if the applied AC frequency is over 200 kHz, the voltage amplifier exhibits rapid attenuation and waveform distortion. Besides, some previous investigations have shown that a larger AC frequency, e.g., above MHz, cannot induce apparent mixing enhancement and turbulent flow . Therefore, all of the experiments are conducted at no more than 200 kHz.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that if the applied AC frequency is over 200 kHz, the voltage amplifier exhibits rapid attenuation and waveform distortion. Besides, some previous investigations have shown that a larger AC frequency, e.g., above MHz, cannot induce apparent mixing enhancement and turbulent flow . Therefore, all of the experiments are conducted at no more than 200 kHz.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, some previous investigations have shown that a larger AC frequency, e.g., above MHz, cannot induce apparent mixing enhancement and turbulent flow. 53 Therefore, all of the experiments are conducted at no more than 200 kHz.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The results showed that this frequency enabled faster and more thorough mixing of liquid samples, allowing for faster enzymatic catalysis reaction. According to our previous results, the lower the frequency, the better the mixing effect, but when the frequency is too low, bubbles will form in the channel, which will block the channel and reduce the mixing efficiency. In the present study, 500 kHz was the optimal frequency that gave the best mixing result without generating any bubbles.…”
mentioning
confidence: 86%
“…Through theoretical and experimental study, we found that voltage, frequency, and conductivity ratio were the key factors that directly affect the μEKT mixing efficiency (Supporting Information: Theory Background). 18 Mixing efficiency could be improved by increasing the voltage and conductivity difference, decreasing the flow rate (Supporting Information Figures S1−S3) and frequency. 18 Therefore, we will study the direct effects of these parameters on the efficiency of biochemical reactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation